Attitudes of medical students toward psychiatry in Eastern Mediterranean Region: A systematic review - Mohebbi, Mohammad; Nafissi, Nastaran; Ghotbani, Farzaneh; Khojasteh Zonoozi, Arash; Mohaddes Ardabili, Hossein (Frontiers in Psychiatry, 2023)
Background Psychiatry is facing one of the highest levels of shortages among medical specialties. Stigma toward psychiatry plays an influential role in medical students' decision to choose psychiatry as a career and has been reported to be prevalent in different parts of the world, particularly in low/middle-income countries. Objective To systematically review the Eastern Mediterranean Region (EMR) medical students' attitudes toward psychiatry, to assess whether their attitudes are stigmatized or not, and the factors affecting their attitudes. Method PubMed, Scopus, Web of Science, and PsychInfo (PsycARTICLES) were searched using a combination of main terms “stigma,” “psychiatry,” “medical students,” and the name of Eastern Mediterranean countries. Cross-sectional studies assessing the attitudes of EMR medical students toward psychiatry were included in this review. Results Ten studies were eligible to be included in the result synthesis. These were from Pakistan (n = 3), Iran (n = 2), Saudi Arabia (n = 1), Lebanon (n = 1), Egypt (n = 1), Bahrain (n = 1), and Oman (n = 1). Most studies reported a combination of both positive and negative attitudes among medical students; however, the overall attitude was positive. Factors affecting medical students' attitude toward psychiatry included poor psychological well-being, having a friend with a psychiatric illness, involving in a romantic relationship with someone suffering from mental illness, young age, frequency of exposure to psychiatry clerkship/teaching, and quality of psychiatry clerkship. Nevertheless, the final positive or negative outcome of these factors on students' attitudes remained controversial. Conclusion Considering the lack of sufficient data from most EMR countries, we need to exercise caution in interpreting the results of this review. Nevertheless, our review indicates that psychiatry is not stigmatized among EMR medical students, and they have generally positive attitudes toward it. The findings of studies evaluating influencing factors are contradictory and demand further exploration.